Gender Inequality and Poverty in Armenia: A Multidimensional Approach - Shahnazaryan, Gohar (Journal of Sociology: Bulletin of Yerevan University, 2022)
A gender perspective highlights that poverty affects women and girls disproportionally due to gender biases, unequal division of power in society and social expectations from the roles of men and women. Starting from the 1980s, feminist researchers had begun to raise the issue of the feminization of poverty, and stressed the importance of the intersectionality between not only poverty and gender, but also poverty, gender, ethnicity, age, marital status, etc. Multidimensional analyses of poverty can become the most appropriate methodological approach to understand interconnections between gender and poverty. In order to reveal the whole spectrum of impacts of poverty on different social groups, a multidimensional analysis focuses on 1) opportunities and choices; 2) resources; 3) power and voice; 4) human security. In the article, poverty among men and women in Armenia is presented and recommendations to mitigate poverty among various women’s groups are presented.